Foliar Application of Boron Boosts the Performance of Tropical Sugar Beet - Bithy, Shritinnahar; Paul, Swapan Kumar; Kader, Md. Abdul; Sarkar, Shubroto Kumar; Mahapatra, Chandan Kumar; Islam, A. K. M. Rashadul (Journal of the Bangladesh Agricultural University, 2024)
The experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh to find out the effect of foliar application of boron on the growth, yield and quality of tropical sugar beet. The treatments included foliar application of boron at four concentrations viz. 0, 50, 100 and 150 ppm, and three application times viz. once at 40 days after emergence (DAE), twice at 40 and 65 DAE and thrice at 40, 65 and 90 DAE. The experiment was laid out in a randomized complete block design with three replications. The SPAD values were increased with advancement of time and reached the maximum (55.99) at 90 DAS with 150 ppm boron applied thrice at 40, 65 and 90 DAE and thereafter declined. Crown rot infestation was suppressed properly when 100 ppm or 150 ppm boron was applied thrice at 40, 65 and 90 DAE. The highest beet length (28.92 cm) was obtained from150 ppm boron applied twice at 40 and 65 DAE while the highest beet girth (36.25 cm), beet yield (104 t ha-1) and shoot yield (6.40 t ha-1) were recorded when 150 ppm boron was foliar applied thrice at 40, 65 and 90 DAE whereas the lowest values were recorded in control treatment. The highest brix percentage (16.33%) was recorded with 100 ppm boron applied thrice at 40, 65 and 90 DAE which was at par with 150 ppm boron applied thrice at 40, 65 and 90 DAE, twice at 40, 65 DAE and once at 40 DAE while the highest purity (75.53 %) was recorded in 150 ppm boron applied thrice at 40, 65 and 90 DAE. Therefore, it can be concluded that foliar spray of 150 ppm boron thrice at 40, 65 and 90 DAE appears as the most effective for maximizing the yield and juice quality of sugar beet. J Bangladesh Agril Univ 18(3): 537–544, 2020 https://doi.org/10.5455/JBAU.121026